The effectiveness of the appreciation of ethics and civilization course in shaping character among students of politeknik Kuala Terengganu - Salmi Mohd; Hazian Ismail; Zainun Binti Salleh (Lentera Negeri, 2024)
Students in the field of Technical and Vocational Education and Training (TVET) generally focus on preparing for the job market with relevant and practical skills. However, this effort becomes more meaningful if they succeed in developing themselves into individuals with high moral character. The process of shaping character involves holistic personal development, including moral, ethical, emotional, social, and intellectual aspects. These characteristics are encompassed in the course on Ethical Appreciation and Civilization (PEP). However, a question arises regarding the extent to which this course impacts students' character. This study aims to explore students' interest and understanding of the PEP course and its effectiveness in shaping their character. The results of the study indicate that students have a high level of interest and understanding of this course. They agree that the course has helped them develop good character. It is the responsibility of all parties involved to ensure that this course continues to be implemented in the teaching and learning processes at higher education institutions (HEIs).